Penyelesaian Pembatalan Akad Istishnaâ€™ Pada Jual Beli Bibit Hortikultura di Desa Pranggang Kecamatan Plosoklaten Kabupaten Kediri Perspektif Kompilasi Hukum Ekonomi Syariah: Completion of Istiá¹£nÄâ€™ Cancellation on Selling and Buying Horticulture Seeds in Pranggang Village, Plosoclaten District, Kediri Regency Perspective Kompilasi Hukum Ekonomi Syariah - Siti Kalimah; Qurrotul Muzdalifah (El-Qist: Journal of Islamic Economics and Business (JIEB), 2022)
This study aims to describe the practice, causes and resolution of the cancellation of the Istiá¹£nÄâ€™ contract in the sale and purchase of horticultural seeds in Pranggang Village, Plosoklaten District, Kediri Regency. Istiá¹£nÄâ€™ contract cancellation was experienced by almost 50% of the sellers out of a total of 48 sellers there. This study uses field research with the type of research that is a case study. The research method uses descriptive qualitative research. The collecting data using the method of observation, interviews and observations. The results of this study are; 1) The practice of the Istiá¹£nÄâ€™ contract on the buying and selling of horticultural plant seeds in Pranggang Village has fulfilled the pillars and conditions of the Istiá¹£nÄâ€™ contract so that the practice of the contract is punished as a valid sale and purchase contract; 2) The factor of cancelling the Istiá¹£nÄâ€™ contract on the sale and purchase of horticultural seeds in Pranggang Village is due to default and overmatch factors; 3) Completion of cancelling the Istiá¹£nÄâ€™ contract on the sale and purchase of horticultural seeds in Pranggang Village is divided into two. That is unilateral cancellation by paying compensation (down payment (DP) is non-refundable) and cancellation on the willingness of both parties (DP is refundable). The completion of the cancellation of the Istishna contract on the sale and purchase of horticultural plant seeds in Pranggang Village, Plosoklaten District, Kediri Regency is in accordance with the settlement according to the Sharia Economic Law Compilation. Â